Determination and Correction of an Inconsistent System of Linear Inequalities (Journal of Computational Mathematics, 1995)
In this paper the problems to determine an inconsistent system of linear inequalities and to correct its right-hand side vector are solved by using the isometric plane method for linear programming. As an example, the suitable perturbation quantity of the perturbed inequalities of ill-conditioned linear equations is determined in the numerical experiments.